Surface modification of poly (ethylene terephthalate) fabric by soy protein isolate hydrogel for wound dressing application. Issue 12 (13th August 2019) - Norouzi, Mohammad-Reza; Ghasemi-Mobarakeh, Laleh; Gharibi, Hamidreza; Meamar, Rokhsareh; Ajalloueian, Fatemeh; Chronakis, Ioannis S.
Abstract: In this study, a composite of poly (ethylene terephthalate) (PET) fabric and soy protein isolate (SPI) hydrogel loaded with gabapentin was developed. For covalent attachment of SPI on the surface of PET fabric, graft polymerization of acrylic acid (AA) on the surface of PET fabric was performed and then carboxyl groups available in the structure of AA were activated using EDAC and then SPI was coated on the surface of PET fabric. The results revealed appropriate connection between hydrogel and modified fabric. The hydrogel was characterized by swelling test and the drug release behavior was investigated. It was found that the casting temperature affects the swelling ratio of the hydrogel and an appropriate release profile of the drug was observed. The surface of fabric was characterized by contact angle measurement, electron microscopy, and infrared spectroscopy. In vitro cell culture study was performed using NIH 3T3 mouse fibroblasts to investigate the biocompatibility of final composite and MTS results along with morphology of cells on the surface of PET fabric coated with SPI revealed the biocompatibility of final product and no cell cytotoxicity was observed in modified PET fabric. Graphical Abstract: